Numerical Solution of Casson Nanofluid Flow Over a Non-linear Inclined Surface With Soret and Dufour Effects by Keller-Box Method - Anwar, Muhammad I.; Rafique, Khurram; Misiran, Masnita; Khan, Ilyas (Frontiers in Physics, 2019)
In this article, Casson Nanofluid boundary layer flow over non-straight slanted extending surface with Soret and Dufour impact scrutinized. Model used in this study is based on Buongiorno model for the thermal efficiencies of the fluid flows in the existence of Brownian motions and thermophoresis properties. The nonlinear problem for Casson Nanofluid flow over inclined channel is modeled to think about the heat and mass exchange phenomenon by considering portent flow parameters to intensified boundary layers. The overseeing nonlinear partial differential equations are changed to nonlinear ordinary differential equations and afterward illustrated numerically by methods for the Keller-Box conspire. A comparison of the established results in the lack of the incorporated effects is performed with the available outcomes of Khan and Pop [1] and recognized in a nice settlement. Numerical and graphical results are also presented in tables and graphs.